Dynamic wettability and contact angles of poly(vinylidene fluoride) nanofiber membranes grafted with acrylic acid (eXPRESS Polymer Letters)
Wettability has been recognized as one of the most important properties of fibrous materials for both fundamental and practical applications. In this study, the plasma induced grafting of acrylic acid (AAc) was applied to improve the wettability of the electrospun poly(vinylidene fluoride) (PVDF) nanofiber membranes. The diameter and chemical structure of the modified PVDF nanofibers were characterized by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR). Nitrogen adsorption based on BET (Brunauer, Emmett and Teller) principle was employed to measure the specific surface areas and porosities of the modified nanofiber membrances. The contact angles of the modified membrane were evaluated by drop shape analysis (DSA) and the modified Washburn method. The dependence of contact angles on specific surface area and porosity was also discussed in this paper. Water adsorptions were used to evaluate the dynamic wetting behavior of the grafted membranes by a dynamic adsorption apparatus (CDCA100-F). The experimental results revealed that the wettablity of the modified PVDF membrane was significantly affected by both surface and porous contact angles.